Rationale and design of a community-based double-blind randomized clinical trial of an HPV 16 and 18 vaccine in Guanacaste, Costa Rica - Herrero, Rolando (2008)
We report the rationale, design, methods and details of participation of a community-based, double-blind, randomized clinical trial of an HPV 16 and 18 vaccine conducted in two provinces of Costa Rica to investigate the efficacy and population impact of the vaccine in the prevention of cervical cancer precursors. More than 24,000 women between 18 and 25 years of age were invited to participate and pre-screened for eligibility, with recruitment of 7466 women (30% of those pre-screened, 59% of those eligible) who were randomized to receive 3 doses of the HPV vaccine or hepatitis A vaccine as control. A complex protocol of data and specimen collection was applied, including an interview, pelvic exam for sexually active women, blood for serology and cell-mediated immunity, cervical secretions for local immunity and cells for HPV, Chlamydia trachomatis and gonorrhea testing. Eighty percent of the women received three doses, 12.4% two doses and 7.4% one dose. At visits, compliance with data and specimen collection was close to 100%. Baseline characteristics and age-specific prevalence of HPV and cervical neoplasia are reported. Overall prevalence of HPV was high (50%), with 8.3% of women having HPV 16 and 3.2% HPV 18. LSIL was detected in 12.7% of women at baseline and HSIL in 1.9%. Prevalence of Chlamydia was 14.2%. There was very good agreement in HPV detection between clinician-collected and self- collected specimens (89.4% agreement for all types, kappa 0.59). Follow up will continue with yearly or more frequent examinations for at least 4 years for each participant.